2021
DOI: 10.1093/pcmedi/pbab014
|View full text |Cite
|
Sign up to set email alerts
|

Applications and challenges of CRISPR-Cas gene-editing to disease treatment in clinics

Abstract: Clustered regularly interspaced short palindromic repeats-CRISPR associated systems (Cas) are efficient tools for targeting specific genes for laboratory research, agricultural engineering, biotechnology, and human disease treatment. Cas9, by far the most extensively used gene-editing nuclease, has shown great promise for the treatment of hereditary diseases, viral infection, cancers and so on. Recent reports have revealed that some other types of CRISPR-Cas systems may also have surprising potential to join t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 151 publications
0
38
0
Order By: Relevance
“…This suggests that a careful combination of viral and nonviral delivery methods may be an alternative approach for cancer treatment in patients. 116 …”
Section: Challenges Of Using Crispr In Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that a careful combination of viral and nonviral delivery methods may be an alternative approach for cancer treatment in patients. 116 …”
Section: Challenges Of Using Crispr In Cancer Treatmentmentioning
confidence: 99%
“…Recently, in a study paired Cas9 nickase has been found to increase HDR efficiency by producing single-strand nicks. 116 …”
Section: Challenges Of Using Crispr In Cancer Treatmentmentioning
confidence: 99%
“…However off‐target mutations while targeting the desired genes are still a reality. Therefore, an improved genome editing system based on CRISPR can overcome certain of these limitations (W. Liu et al, 2021). A base editing technique was developed to induce precise editing, but unfortunately, it can only correct four single‐base mutations (Abdullah et al, 2020).…”
Section: Conventional Genome Editing Strategiesmentioning
confidence: 99%
“…RNP shows improved stability, rapid action, low off-target effects, low immunogenicity, and no risk of insertional mutagenesis, despite its high cost and relatively short gene editing duration [36,41,42]. Therefore, depending on specific applications and requirements, all these three formats have been widely explored for many biomedical applications, including therapies for cancer as well as genetic, infectious, and immunological diseases [14,[43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%